The significant contribution of stochastic forcing to nonlinear energy transfer in resolvent analysis - Wang, Youhua; Wu, Ting; He, Guowei (Theoretical and applied mechanics letters, 2025)
•Nonlinear energy transfer of resolvent analysis presented.•Demonstrating the contribution of stochastic forcing cannot be ignored.•Prediction of nonlinear energy transfer improved in composite resolvent. [Display omitted] Nonlinear energy transfer is represented through eddy viscosity and stochastic forcing within the framework of resolvent analysis. Previous investigations estimate the contribution of eddy-viscosity-enhanced resolvent operator to nonlinear energy transfer. The present article estimates the contribution of stochastic forcing to nonlinear energy transfer and demonstrates that the contribution of stochastic forcing cannot be ignored. These results are achieved by numerically comparing the eddy-viscosity-enhanced resolvent operator and stochastic forcing with nonlinear energy transfer in turbulent channel flows. Furthermore, the numerical results indicate that composite resolvent operators can improve the prediction of nonlinear energy transfer.